PENERAPAN PEMBELAJARAN ELEARNING UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA TERHADAP MATA KULIAH PERENCANAAN PEMBELAJARAN DI PGSD FKIP UNSYIAH - Mislinawati Mislinawati. (Jurnal Pesona Dasar, 2019)
In accordance with the demands of technological and information development lecturers arerequired to make innovation in learning. One of the innovation that lecturers can apply intheir teaching is learning through the use of e-learning. The approach in this study usedqualitative research with the research subjects of the Unsyiah FKIP PGSD students whoattended the learning planning course. The technique of data collection is done throughobservation and interviews. The results of the study show that students can understand thematerial well through e-learning. With various forms of material used such as modules, PPTand video can help students understand the material of each topic. The conclusions in thisstudy through the use of e-learning can improve students' understanding of learning planningcourses. This can be seen from the scores of the assignments and the quiz that is done oneach topic gets good grades.